Metal ion-catalyzed interfacial polymerization of functionalized covalent organic framework films for efficient separation. (20th April 2023) - Qu, Yanqing; Zha, Yuxin; Jia, Hongge; Zang, Yu; Liu, Yang; Gu, Tong; Du, Xiaoyu
Graphical abstract: Highlights: High permeability and excellent selective rejection of dyes has been realized by permeation of new COF membranes. Four flexible imine-linked freestanding COF membranes with different thicknesses and morphologies showed high performance. The diameter of the continuous area of COF membranes can be adjusted according to the size of the vessel without supporting. Metal catalyst-catalyzed liquid-liquid interfacial polymerization (IP) is an effective method for COF membrane synthesis. Metal catalyst-catalyzed liquid IP process is expected to facilitate the up-scaling of COF-based membranes. Abstract: Covalent organic frameworks (COFs), with high porosity, uniform and tunable pore size, which are advantageous to prepare defect-free membranes with high separation performance and high permeability, and have achieved efficient applications in the field of separation membranes in numerous directions. According to our knowledge, the transition metal ion (Cu 2+ ) which is used in Schiff base condensation reaction has been rarely described. Herein, we report the interfacial polymerization of ternary amines and binary aldehyde monomers via the catalyst Cu(ClO4 )2 ·6H2 O. In this work, we report the fabrication of covalent organic framework films from four different functional structure monomers by using the transition metal ion-catalyzed interfacial polymerization at room temperature. The four as-synthesized films are flexible, continuous, defect-free and have large areas, which have excellent performance in the direction of dye separation as well as solvent penetration. After the COF films were transferred to the polyethersulfone support, the composite films exhibited enhance the rejection of methylene blue (98.43%), high-water flux (81.46 L m −2  h −1 bar −1 ) and solvent flux (ethanol (13.03 L m −2  h −1 bar −1 ), acetonitrile (50.38 L m −2  h −1 bar −1 )). The large area, tunable pore size, and tailored molecular composite membranes show potential for nanofiltration applications.